Rendang Lokan as A Culinary Tourism Attraction in Pesisir Selatan - Nadra, Abdiani Khairat; Nora, Efmilia (Journal of Business on Hospitality and Tourism, 2020)
The tourism trend in which culinary tourism is one of the favorite tourist attractions that is favored provides opportunities for areas that have distinctive culinary delights, Pesisir Selatan is one of the areas that has traditional culinary specialties which if developed will become one of the tourist attractions. This study aims to see whether the culinary specialties of Pesisir Selatan Rendang Lokan has the potential to be developed as a tourist attraction. This research is descriptive with a qualitative approach, using Damanik and Weber's theory of uniqueness, originality, authenticity and diversity and is supported by Yoeti's theory of tourist attraction, namely having something to see, something to do and something to buy. Data collection was carried out by interview and observation. The results showed that Rendang Lokan has the potential to be developed as a tourist attraction. This can be seen from the uniqueness of its taste, its originality and consistency in the use of the same ingredients that has not changed since the past, its authenticity in the traditional manufacturing process, and its diversity on its flavors. As a tourist attraction, Rendang Lokan also meets the criteria of "Something to be seen" which is the process of making and processing ingredients and spices. It also has "Something to do" which is being able to involve tourists to join in cooking Rendang Lokan, and also "Something to buy" which acts as a souvenir.